Patients’ Attitudes, Awareness, and Opinions About Community Pharmacies in Japan: Next Steps for the Health Support Pharmacy System - Hirota N; Okamura N (Dove Medical Press, 2020)
Noritake Hirota,1,2 Noboru Okamura1 1Department of Clinical Pharmacy, School of Pharmaceutical Sciences, Mukogawa Women’s University, Nishinomiya, Japan; 2General Incorporated Association Osaka Pharmaplan, Aozora Pharmacy, Osaka, JapanCorrespondence: Noritake HirotaGeneral Incorporated Association Osaka Pharmaplan, Aozora Pharmacy, 3-6-8 Nozato, Nishiyodogawa-Ku, Osaka City, Osaka 555-0024, JapanTel +81-6-6477-8088Fax +81-6477-8090Email n-hirota@faruma.co.jpPurpose: Despite the formal establishment of the Health Support Pharmacy system, few community pharmacies have transitioned to this new designation in Japan. Moreover, patients’ perspectives on the usefulness of health-support pharmacies and community pharmacies have not yet been investigated. In this work, we investigated patients’ attitudes, opinions, and awareness as users of member pharmacies of the Japan Federation of Democratic Medical Institutions (Min-Iren), with respect to two essential functions provided by community pharmacies—primary care and health support—to identify modern challenges facing community pharmacies.Methods: Regular visitors to participating Min-Iren community pharmacies were asked to complete an anonymous questionnaire. Responses were compared between users of health-support pharmacies and other pharmacy types, as well as between members and non-members of “collaborating organizations” (CO). CO is organizational partners of Min-Iren whose activities support affiliated facilities. Logistic regression analysis was performed to explore the predictive value of different factors on pharmacies’ primary-care and health-support functionality.Results: A total of 181 Min-Iren community pharmacies (51.7%: 181/350) participated in this study, and most patients answered the questionnaire (97.7%, n=2623). Relatively few patients recognized the term “Health Support Pharmacy” (12.2%). CO members tended to have a superior understanding of a wide variety of services provided by CPs as compared to non-members. Statistically significant predictors of primary-care and health-support functionality included male gender, having a primary-care pharmacist, age ≥ 60 years, recognition of the term “Health Support Pharmacy” and CO membership.Conclusion: CO members, a class of patients with a superior awareness of health promotion, demonstrated a good understanding of the variety of services provided by community pharmacies and tended to positively rate their pharmacy. Moving forward, efforts to raise awareness about the importance of health-promotional activities among community pharmacy users should further reinforce the primary-care and health-support functions of community pharmacies.Keywords: community pharmacy, health-support pharmacy, primary-care function, health-support function, patient awareness